Prevalence of genital infections among women in reproductive age group in a rural area in North Kerala - Thomas, Enid Elizabeth; Kumaran, Jayasree Anandabhavan (International Journal Of Community Medicine And Public Health, 2019)
Background: Genital infections, a major cause of illness among women in reproductive age group, affect their quality of life and social living. Early diagnosis and treatment of STI/RTI is also an important aspect in prevention of HIV transmission. As there are only a handful of studies in Kerala and none in Kannur assessing the prevalence, associated factors of genital infections and health seeking behaviour among women in reproductive age group, this study stands important. Methods: A community based descriptive study was conducted in Kulappuram area of Cheruthazham Panchayat which is the field practice area of Department of Community Medicine, Government Medical College, Kannur, Pariyaram from June, 2017 – July, 2018. A total of 404 women in reproductive a group were studied. A semi-structured, pre-tested questionnaire was used to collect relevant information. Data was analyzed using SPSS-version 19 software. Results: The mean age of the study population was 32.20±10.741years. 52.7% of the study population had genital infection, with 40.6% having symptoms of Reproductive Tract Infections (RTI) and 12.1%, symptoms of Urinary tract Infections (UTI). The presence of these was significantly associated with menstrual disorders, cloth as menstrual pad users, marriage, sexual activity and absence of infertility. Only 39.0% of the women with infections had sought treatment. Conclusions: Although there was high prevalence of genital infections among the study population, treatment seeking behaviour was very low. There is a need for sustained motivation and support to promote women to seek timely medical care than to suffer silently.